Impacts of Climate Change on Canadian Airport Pavements - Abreu, Edward Alexander (University of Waterloo, 2019)
Greenhouse gasses (GHG) emitted by the burning of fossil fuels and supplementary anthropogenic activities are on the rise since the industrial revolution. The world is becoming warmer and more polluted with such gases, which have also caused notable changes in the climate. The environment has been affected by this situation and Canadian airports are no exception. This research aims to present numerous changes of climate at different airports located in various provinces and territories of Canada. The extent of precipitation and risk of flooding, the highest and lowest annual temperatures, the fluctuation of freeze-thaw cycles, and the variation of permafrost are all considered. In addition, this research analyzes the impact of these changes on the operation and/or performance of the airside infrastructure at the selected airports and provides recommended considerations for mitigation and adaptation strategies. The correlation between the changes in climate and the impacts of these to the airfield infrastructure was assessed by an array of laboratory tests in which the samples were subjected to conditions simulating: moisture damage, rise of temperature, and the fluctuation of freeze-thaw cycles. The Hamburg wheel tracking test (HWTT) was performed to evaluate rutting under various temperatures as well as different quantities of freeze-thaw cycles. The tensile strength ratio (TSR) was developed to assess the reduction of indirect tensile strength (ITS) due to freeze-thaw cycles. The ITS results were used to calculate a crack propagation index called IDEAL CT-Index which provided insights into how freeze-thaw cycles affect the crack propagation of flexible airfield pavement infrastructures. The findings of the research indicate that Canadian airports are indeed experiencing a rise of both the maximum and the minimum temperature which is inducing the amount of rainfall to rise as well. Snowfall, on another hand, is varying depending on the locations, being Montreal airport the one experiencing the largest reduction ...